TRABALHO E FORMAÇÃO NA PERSPECTIVA DA BURGUESIA INDUSTRIAL - Celso do Prado Ferraz de Carvalho (EccoS – Revista Científica)
This article aims to present research findings on the relationship between university and company, being analyzed from the history of an organic institution of the bourgeoisie, the Euvaldo Lodi Institute, estabilished in 1969 and financially supported by the National Confederation of Industry (CNI in Portuguese). We intend to show the Institute as a part of a bigger bourgeoisie moviment, bringing influence to public politics definition in order to transform the university into a place that attends industry interests. Considering a Gramsci¿s perspective of the organic intellectual, the research analyzes transformation both in the Institute directors¿ discourse and in their speech in diferent times and its relation with changes in CNI board of directors and with the country´s political circumstances. Finally, it shows how the Institute has participated during 1990 decade, the dissemination of Total Quality Education theory time, delineating a new appproach and redefining their praxis and action.